Reconstructing the Surge History and Dynamics of Fisher Glacier, Yukon, 1948-2022 - Partington, Gabriel (Université d'Ottawa / University of Ottawa, 2023)
Glacier surges are periods of dynamic instabilities which result in semi-regular alternating periods of slow flow, termed the quiescent phase, and fast flow, termed the active phase. This study uses remotely sensed imagery, digital elevation models, glacier velocity datasets, and in situ oblique photographs to reconstruct the surge history and dynamics of Fisher Glacier to better characterize surging in the southwest Yukon and assess the risk posed by this glacier’s surges on surrounding regions. Fisher Glacier has previously been identified as a surge-type glacier but, until now, it had not been the focus of any detailed studies. We find evidence that Fisher Glacier underwent two surges during the study period from 1948 to 2022. Visual analysis of characteristic surge features on the glacier surface show that the glacier was in quiescence from <1948 to at least 1963. In 1972, an advanced terminus position, intense surface crevassing, and high point velocities suggest that a surge had recently terminated, corroborating a previous report of a surge occurring around 1970. This was followed by a 40-year quiescent phase from ~1973-2013 during which the terminus underwent consistent retreat, totaling a terminus-wide average of 2058 ± 8 m (up to 3567 ± 8 m in certain sections). Velocities during the quiescent phase were low (generally <50 m yr⁻¹), but underwent a slow multidecadal increase starting around 1985, spreading from the center of the glacier towards the head and the terminus. A pre-surge buildup phase beginning in ~2008-2010 resulted in velocities of up to ~200 m yr⁻¹. The active phase of the surge initiated in winter 2013/14 and was characterised by a velocity increase to ~1500 m yr⁻¹ that propagated both up- and down-glacier from the surge nucleus in the mid-region (~22 km upglacier from the terminus). Velocities peaked at >2100 m yr⁻¹ in the winter/early spring of 2016 at ~12 km from the terminus. The surge resulted in a mean terminus-wide advance of 868 ± 8 m, intense surface crevassing and a ...